Teaching Soil Color Determination Using an Inexpensive Color Sensor. Issue 1 (20th December 2016) - Stiglitz, R. Y.; Mikhailova, E. A.; Post, C. J.; Schlautman, M. A.; Sharp, J. L.
Abstract : Core Ideas: Soil color is indicative of many soil characteristics. This article describes teaching students color identification using traditional Munsell color chart and sensor based technology. Students preferred using a soil color sensor over a color chart. As new technologies are introduced to soil science it is important to determine the potential and preference for such innovations among users. The Nix Pro color sensor, an inexpensive mobile color sensor, was tested by college students for its ability to determine soil color in comparison with the use of a traditional Munsell color chart. Sixty‐four Clemson University students from various fields of study (forestry, wildlife biology, and environmental and natural resources) had a hands‐on experience with the Nix Pro color sensor and the Munsell color chart during FNR 2040: Soil Information Systems course taught in the fall of 2015. Students completed a laboratory exercise to determine soil color using the two methods of color determination (Munsell color chart and Nix Pro). Students then filled out a survey providing answers to 15 questions related to their previous experience with soil color analysis, the ease of use of the two color analysis methods, and which method of color analysis they preferred. Eighty‐three percent of the students preferred to use the Nix Pro color sensor over the Munsell color chart, 76% judged the Nix Pro to be less subjective to environmental conditions, and 91% believed the Nix Pro to be less subjective to user sensitivities. Student responses to survey questions regarding use of the Nix Pro color sensor were positive overall, indicating that there is great potential in using the new color sensor in teaching soil science. Impact Statement We taught students in an introductory‐level soil science course different methods of color analysis. A questionnaire provided after the lab exercise showed that 83.1% of the students preferred the Nix Pro color sensor over the Munsell color chart. The average student found the Nix Pro color sensor very easy to use, and many students reported that they enjoyed the laboratory experience. The overall results of the questionnaire indicate that the Nix Pro is a valuable teaching device and that students are receptive to learning the importance of soil color analysis and its methods.